A Review on Enhancement of IoT devices for Traffic Management System - Mr.Ameya K. Kulkarni; Ms.Deepali A.Ghanwat (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In a new era in a new era, Traffic has drastically enhanced in metropolitan cities. traffic leads with growth in air and noise pollutants, motion time and fuel wastage and plenty of others.The serious trafic congestion that causes signal disasters, injuries etc. this stuff have an effect on to economic expenditure, changes in approach of lifetime of humans and plenty of others. Internet of things will assist in clean implementation of Traffic congestion control system. Essentially the design is split into modules in conjunction with WiFi Sensors, video process, IoT device Security